Method for Estimation of Calcium Carbonate in Soils from Iraq - Kassim, Jabbar K (International Journal of Environment, 2013)
Attempts have been made to evaluate four methods of quantitative determination of soil carbonates. Calcium carbonates equivalent were determined by the acid neutralization, calcimeter and acetic acid methods. Also, it obtains by the fourth methods when the acid neutralization method is corrected against proton adsorption. The acid neutralization method gave significantly higher estimates of total carbonates and different from each of the others. The calcimeter method gave the lower estimates of CaCO3 equivalent. The results showed that the corrected values of CaCO3 equivalent did not differ significantly from other three methods but the overall mean tended to be higher than the acetic acid and calcimeter methods. It may be concluded that the acetic acid method is simple, can reasonably estimate the carbonate content and requires only a pH meter. It can be used for routine determination of soil carbonate. DOI: http://dx.doi.org/10.3126/ije.v1i1.8524 International Journal of Environment Vol.1(1) 2013: 9-19